2013
DOI: 10.1371/journal.pone.0053531
|View full text |Cite
|
Sign up to set email alerts
|

The Mincle-Activating Adjuvant TDB Induces MyD88-Dependent Th1 and Th17 Responses through IL-1R Signaling

Abstract: Successful vaccination against intracellular pathogens requires the generation of cellular immune responses. Trehalose-6,6-dibehenate (TDB), the synthetic analog of the mycobacterial cord factor trehalose-6,6-dimycolate (TDM), is a potent adjuvant inducing strong Th1 and Th17 immune responses. We previously identified the C-type lectin Mincle as receptor for these glycolipids that triggers the FcRγ-Syk-Card9 pathway for APC activation and adjuvanticity. Interestingly, in vivo data revealed that the adjuvant ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
126
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(135 citation statements)
references
References 36 publications
5
126
2
Order By: Relevance
“…In contrast, we and others observed intact in vitro activation of macrophages or granulocytes by TDM or TDB in the absence of MYD88, arguing against a role for TLR (7,11,12). In vivo, glycolipid adjuvant activity depends on MYD88 signaling (3,6), which is at least partially due to IL-1R signaling but independent of TLR2/3/4/7/9 (13).…”
contrasting
confidence: 69%
See 1 more Smart Citation
“…In contrast, we and others observed intact in vitro activation of macrophages or granulocytes by TDM or TDB in the absence of MYD88, arguing against a role for TLR (7,11,12). In vivo, glycolipid adjuvant activity depends on MYD88 signaling (3,6), which is at least partially due to IL-1R signaling but independent of TLR2/3/4/7/9 (13).…”
contrasting
confidence: 69%
“…TLRindependent functions of the MYD88 adapter protein can also contribute to TDB/TDM responses in vivo, as the adjuvant effect of TDB is independent of TLR2/3/4/7 but requires MYD88 (6). We recently tested the role of the MYD88-utilizing cytokines IL-1, IL-18, and IL-33 for adjuvanticity of TDB, and identified an important contribution of IL-1R signaling (13). Similar findings of TLR-independent, but IL-1R-Myd88-dependent, in vivo adjuvanticity have been reported by Sher's group (56) for CFA.…”
Section: Discussionmentioning
confidence: 99%
“…TDB induces strong T H 1 and T H 17 immune responses and the C-type lectin Mincle is the receptor for APC activation. The adjuvant effect also requires MyD88 and Schweneker and colleagues identified the Nlrp3 inflammasome as mediator for TDB-triggered induction of immune response [Werninghaus et al 2009;Desel et al 2013;Schweneker et al 2013]. Properties of cationic liposome-forming lipids were studied with rigid DDA or fluid dimethyldioleoylammonium (DODA) liposomes.…”
Section: Cationic Liposome Adjuvant Vaccinesmentioning
confidence: 99%
“…Molecular mechanisms of TDB/TDM adjuvanticity were identified to be strictly Mincle-dependent and strong IL-17 production post immunization controls the generation of cellular immunity. 31,32 Desel et al 32 showed that adjuvanticity of TDM/TDB not only depends on Mincle, but also necessitates MyD88. Whereas in vitro studies identified MyD88 independence, in vivo adjuvanticity was strongly dependent on MyD88 signaling.…”
Section: Antigen Delivery and Immune-stimulationmentioning
confidence: 99%